2015
DOI: 10.1371/journal.pone.0124481
|View full text |Cite
|
Sign up to set email alerts
|

Cambinol, a Novel Inhibitor of Neutral Sphingomyelinase 2 Shows Neuroprotective Properties

Abstract: Ceramide is a bioactive lipid that plays an important role in stress responses leading to apoptosis, cell growth arrest and differentiation. Ceramide production is due in part to sphingomyelin hydrolysis by sphingomyelinases. In brain, neutral sphingomyelinase 2 (nSMase2) is expressed in neurons and increases in its activity and expression have been associated with pro-inflammatory conditions observed in Alzheimer’s disease, multiple sclerosis and human immunodeficiency virus (HIV-1) patients. Increased nSMase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 56 publications
1
79
0
Order By: Relevance
“…These disruptions in cellular energetics could explain abnormal accumulation of sphingolipids and proteins, such as amyloid-β, in dysfunctional endolysosomal compartments 72,75,76,80,127129 : reduced or modified cellular energy production would impair the function of the proton pumps that are dependent on adenosine triphosphate (ATP) — these pumps are necessary to maintain an acidic luminal pH, which is required for efficient functioning of >50 hydrolytic enzymes in lysosomes that degrade cellular products 128,130,131 . The discussed studies have identified several possible targets for therapeutic intervention that include modulators of glucose metabolism (intranasal insulin), ceramide metabolism 72,132,133 and endolysosomal function 131 . Small-molecule therapeutics designed to affect these targets are in early to mid-stage development 131,134 , and a clinical trial is planned to determine the effectiveness of intranasal insulin to treat ANI and MND in HIV+ patients.…”
Section: Pathogenesis In Handmentioning
confidence: 99%
“…These disruptions in cellular energetics could explain abnormal accumulation of sphingolipids and proteins, such as amyloid-β, in dysfunctional endolysosomal compartments 72,75,76,80,127129 : reduced or modified cellular energy production would impair the function of the proton pumps that are dependent on adenosine triphosphate (ATP) — these pumps are necessary to maintain an acidic luminal pH, which is required for efficient functioning of >50 hydrolytic enzymes in lysosomes that degrade cellular products 128,130,131 . The discussed studies have identified several possible targets for therapeutic intervention that include modulators of glucose metabolism (intranasal insulin), ceramide metabolism 72,132,133 and endolysosomal function 131 . Small-molecule therapeutics designed to affect these targets are in early to mid-stage development 131,134 , and a clinical trial is planned to determine the effectiveness of intranasal insulin to treat ANI and MND in HIV+ patients.…”
Section: Pathogenesis In Handmentioning
confidence: 99%
“…In fact, previous studies showed that the IC 50 of GW4869 and Cambinol are 1 and 5 μM respectively [33,65]. Thus, at the same concentration, GW4869 is more effective than Cambinol.…”
Section: Discussionmentioning
confidence: 92%
“…Cambinol is another inhibitor of neutral sphingomyelinase 2, which blocks exosome production [33]. Similar to GW4869, the Ishikawa cells were treated with cambinol at concentrations of 0.1 μM, 1 μM, 10 μM or 30 μM in 5% EVs-depleted-BSA for 48 hours and the EVs were isolated by PBP.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, screening of pharmacologically active compounds for activity against human N-SMase2 has led to the identification of cambinol as a novel uncompetitive N-SMase2 inhibitor. Cambinol modulates TNF-a or IL-1b-induced increase in ceramide and cell death in primary neurons, suggesting it could prevent ceramide-dependent neurodegeneration [200]. The above inhibitors could be valuable lead compounds for development as potent and tolerable inhibitors of aSMase and N-SMase, that can cross the blood--brain barrier.…”
Section: Expert Opinionmentioning
confidence: 99%